Determinants of subnational party positions on electricity grid expansion in Germany: Economic over political interests. (June 2019) - Fink, Simon; Bartels, Jan-Eric; Hagendorf, Winona; Klinger, Niklas
Abstract: The German energy transition necessitates the expansion of the electricity transmission grid. Grid expansion is governed jointly by the federal government and the governments of the subnational states. Conflicts often erupt about the routing of grid projects. This article asks how German subnational parties form their positions on grid expansion. Based on a quantitative analysis of party manifestos, we conclude that the position of the federal party has little influence. Instead, German subnational party preferences are shaped by the energy production structure of their state. The more wind energy a state produces, the more in favour of grid expansion are its parties. Thus, the conflict over grid expansion will most likely persist. The article highlights a paradox of energy policy in a federal system: German federalism has encouraged the expansion of renewable energies, but is detrimental to coherent grid expansion for their utilization. Highlights: Expansion of the electricity grid is necessary for the German energy transition. However, stable subnational party preferences impede grid construction. Paradoxical effect of the federal structure: On the one hand, it encouraged the expansion of renewable energies, on the other hand, it impedes the construction of the necessary electricity grid.